(untitled) (International Journal of Engineering and Computer Science, 2014)
Hospital supervision or healthcare administration is the field with reference to management, leadership and administration of hospitals, health care systems and hospital networks. Healthcare business these days generates huge amounts of complicated information concerning with patients, medical devices, electronic patient records and sickness designation, hospital resources etc. The huge amounts of data’s information and knowledge may be a key resource to be processed and analyzed for knowledge extraction that permits support for cost-savings and higher cognitive process. Data mining brings a collection of tools and techniques that may be applied to the present processed data’s information to getting hidden patterns that offer healthcare professionals an additional or extra source of information and knowledge for better decisions for the administration.